2015
DOI: 10.1039/c5ra08061d
|View full text |Cite
|
Sign up to set email alerts
|

Band-gap tuning of graphene by Be doping and Be, B co-doping: a DFT study

Abstract: First-principles density functional theory (DFT) calculations were carried out to investigate the structural and electronic properties of beryllium (Be) doped and, Be with boron (B) co-doped graphene systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
62
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 58 publications
7
62
2
Order By: Relevance
“…2a. These values are in excellent agreement with some reported theoretical 33 and experimental 55 results. The calculated band structure of the optimized pristine structure of graphene is presented in Fig.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…2a. These values are in excellent agreement with some reported theoretical 33 and experimental 55 results. The calculated band structure of the optimized pristine structure of graphene is presented in Fig.…”
Section: Resultssupporting
confidence: 82%
“…They found that below 0.5% impurity concentration, S-doped graphene has a band gap in the range of 0.1-0.2 eV while P-doped graphene has a higher gap between 0.3 -0.4 eV. Recently, Ullah et al 33 investigated structural and electronic properties of Be and Be/B dual doped graphene via density functional theory calculations, and remarked that with a rectangular doping configuration a maximum band gap of 1.44 eV can be obtained for Bedoped graphene at 12.5 % impurity concentration. Moreover a maximum band gap of 0.99 eV can be attained for Be-B co-doped graphene at the same concentration.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations